2020
DOI: 10.3390/molecules25010237
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biological Evaluation of CK2 Allosteric Fragments through Structure-Based Virtual Screening

Abstract: Casein kinase II (CK2) is considered as an attractive cancer therapeutic target, and recent efforts have been made to develop its ATP-competitive inhibitors. However, achieving selectivity with respect to related kinases remains challenging due to the highly conserved ATP-binding pocket of kinases. Allosteric inhibitors, by targeting the much more diversified allosteric site relative to the highly conserved ATP-binding pocket, might be a promising strategy with the enhanced selectivity and reduced toxicity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…97 However, there has been one report of an inhibitor that is proposed to bind in the αD site allosterically inhibiting CK2α. 98 Unfortunately, there is currently no structural data confirming that this compound binds in the αD site. Therefore, no reliable conclusions can be drawn from this data as to whether the αD site alone can be used as an allosteric site.…”
Section: Inhibitors Of Ck2α Acting Outside the Atp Pocketmentioning
confidence: 99%
See 1 more Smart Citation
“…97 However, there has been one report of an inhibitor that is proposed to bind in the αD site allosterically inhibiting CK2α. 98 Unfortunately, there is currently no structural data confirming that this compound binds in the αD site. Therefore, no reliable conclusions can be drawn from this data as to whether the αD site alone can be used as an allosteric site.…”
Section: Inhibitors Of Ck2α Acting Outside the Atp Pocketmentioning
confidence: 99%
“…11) was identified as the most promising non-ATP competitive inhibitor of CK2α with an IC 50 of 13.0 μM and it was shown to stop the proliferation of A549 cancer cells (GI 50 of 23.1 μM). 98 The authors found that the IC 50 value did not depend on the concentration of ATP used and concluded that such a compound was acting via a non-ATP-competitive mechanism. Computational studies suggested the compound was binding in the αD pocket, 98 but this is still to be demonstrated experimentally.…”
Section: Inhibitors Of Ck2α Acting Outside the Atp Pocketmentioning
confidence: 99%
“…Competition experiments further confirmed that CAM4712 was the potent and selective allosteric inhibitor by binding in the αD pocket without facilitatingcellular uptake. Besides the above mentioned αD-site binding inhibitors CAM4066 and CAM4712, our group identified the novel allosteric inhibitors of CK2α using the pharmacophore model and Alloscore-based virtual screening of ChemBridge fragment library [39]. By considering the filtration of fit values > 2.5 with the αD pocket pharmacophore model, as well as the Alloscore value of 5.8, compound 11 combined with the uracil group was discovered to be an allosteric inhibitor of CK2α (IC50 = 13.0 μM), which is similar to that of CAM4712.…”
Section: Cam4066 Derivatives and Uracil Analoguestargeting Sitementioning
confidence: 99%
“…Despite the inspiring clinical benefits, kinase inhibitors are still encountered an unsurmountable challenge hallmarked by kinase selectivity profile. This is because that the vast majority of protein kinase inhibitors bind to the conserved ATP-binding site, leading to the poor selectivity of kinase inhibitors towards a unique kinase ( Wu et al, 2015 ; Chen et al, 2020 ; Li C. et al, 2020 ). For example, Davis et al (2011) have previously explored the interaction of 72 kinase inhibitors with 442 kinases representing >80% of the human catalytic protein kimome and found that the kinase inhibitor selectivity profile is relatively narrow, with 10%–40% of inhibitors interacting with >60% of kinases, and each inhibitor interacting with more than one kinase.…”
Section: Introductionmentioning
confidence: 99%